Competing pathways for photoremovable protecting groups: the effects of solvent, oxygen and encapsulation - Field, Thomas (2021)
Extending the applications of Photoremovable Protecting Groups (PPGs) to "cage" phenols has generally met with unusually complex PPG byproducts. In this study, we demonstrate that thep-hydroxyphenacyl (pHP) cage for both simple and complex phenolics, including tyrosine, dispenses free phenols. With the simpler unsubstituted phenols, the reaction is governed by their Bronsted Leaving Group ability. On the other hand, the byproducts of the cage vary with these phenols. For the more acidic phenols the cage byproduct follows the Favorskii rearrangement to formp-hydroxyphenylacetic acid whereas for the weaker phenols other reactions such as reduction and hydrolysis begin to emerge. When the photolysis is conducted in octa acid (OA) containers, non-Favorskii, unrearranged fragments of the cage and other byproducts arise.